2014
DOI: 10.1007/s11356-014-3255-3
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater-surface water interactions in the hyporheic zone under climate change scenarios

Abstract: Slight changes in climate, such as the rise of temperature or alterations of precipitation and evaporation, will dramatically influence nearly all freshwater and climate-related hydrological behavior on a global scale. The hyporheic zone (HZ), where groundwater (GW) and surface waters (SW) interact, is characterized by permeable sediments, low flow velocities, and gradients of physical, chemical, and biological characteristics along the exchange flows. Hyporheic metabolism, that is biogeochemical reactions wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 119 publications
1
18
1
Order By: Relevance
“…This observation is consistent with previous studies (Cherkauer and Lettenmaier 1999). However, contrary to what would be expected, rainfall (less than 12 mm/day) and ET 0 had little impact on the seasonal variation of groundwater levels, which was inconsistent with previous studies conducted in frozen soil regions (Chen et al 2004;Hoque et al 2007;Dragoni et al 2008;Zhou et al 2014). However, contrary to what would be expected, rainfall (less than 12 mm/day) and ET 0 had little impact on the seasonal variation of groundwater levels, which was inconsistent with previous studies conducted in frozen soil regions (Chen et al 2004;Hoque et al 2007;Dragoni et al 2008;Zhou et al 2014).…”
Section: Dominant Factors Affecting the Seasonal Variation Of Groundwsupporting
confidence: 48%
“…This observation is consistent with previous studies (Cherkauer and Lettenmaier 1999). However, contrary to what would be expected, rainfall (less than 12 mm/day) and ET 0 had little impact on the seasonal variation of groundwater levels, which was inconsistent with previous studies conducted in frozen soil regions (Chen et al 2004;Hoque et al 2007;Dragoni et al 2008;Zhou et al 2014). However, contrary to what would be expected, rainfall (less than 12 mm/day) and ET 0 had little impact on the seasonal variation of groundwater levels, which was inconsistent with previous studies conducted in frozen soil regions (Chen et al 2004;Hoque et al 2007;Dragoni et al 2008;Zhou et al 2014).…”
Section: Dominant Factors Affecting the Seasonal Variation Of Groundwsupporting
confidence: 48%
“…We deduce that adjacent polluted shallow groundwater, with relatively high concentrations of nutrients due to intensified agricultural activities (Chen et al, ; Li et al, ), affected the nutrient contents in the deep sediments of the southern, western, and northern zones, possibly through upwelling flow. Upwelling flow usually carries relatively high N and P concentrations from deep to shallow sediments, and these concentrations are exchanged with the overlying water (Ammar et al, ; Zhou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Seasonal changes in temperature in the hyporheic zone strengthen or weaken nitrification, denitrification, mineralization, and microbial activity (Hu, Li, Xie, Deng, & Chen, ; Zhou et al, ). The temperature observations in this study showed that the temperature at the sediment surface and a depth of 20 cm were, on average, 5.1–7.5 and 8.2–10.8°C in the 2nd investigation and 11.3–13.2 and 9.8–12.9°C in the 1st investigation, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ground water temperatures tend to be more stable than surface temperatures, thereby effectively buffering stream temperature from rapid changes in air temperature [e.g. Caissie, 2006;Kaushal et al, 2010;Zhou et al, 2014]. As such, our reach-level random effect of air temperature may indicate relative groundwater input, but would reflect a combination of the amount of ground water and the depth or temperature of that ground water relative to the surface temperature.…”
Section: Discussionmentioning
confidence: 99%